An electromagnetic energy harvester for applications in a high-speed rail pavement system. (1st April 2023) - Cao, Hao; Kong, Lingji; Tang, Minfeng; Zhang, Zutao; Wu, Xiaoping; Lu, Linhai; Li, Dongyang
Highlights: An electromagnetic energy harvester with double-rocker mechanism is designed. Halbach array magnet enhances the stability of the system and improves the output power. The dynamic coupling model of flywheel system under low frequency vibration is explored. The proposed system can improve average power by 49.45 % compared with no flywheel system. The pavement block obtained the maximum voltage of 54.4 V and the output power of 1.034 W in real field test. Abstract: Energy harvesting from ambient environment is one of the effective solutions to supply power for low power electronic devices. There are still some challenges such as poor space utilization and low power density for pavement energy harvesters. In this paper, an electromagnetic energy harvester with the double rockers is proposed to harvest the human footstep energy from high-speed rail pavement environment. Combined with two one-way bearings, the proposed double-rocker structure converts up and down motion of plate into a unidirectional rotation motion of the shaft. As the effect of the inertia flywheel, the velocity attenuation of the shaft of generator is slowed down. The dynamic model of the energy harvester with the engagement and disengagement phase is explored. Moreover, the input force and the angular velocity are simulated under the input of the various sinusoidal displacements and frequencies. The simulation and experimental results show that it can obtain the maximum output power of 466.6 mW under the vibration frequency of 5 Hz and the displacement of 10 mm. Further, the inertia flywheel can enhance the system stability and achieve the improvement of average output power by 49.45 % compared with no flywheel system. A pavement block with four energy harvesters is assembled and the actual field test proves it can obtain the maximum voltage of 54.4 V and the output power of 1.034 W, which proves the proposed electromagnetic energy harvester has great potential to achieve self-powered monitoring system and power for the low power electronic devices in high-speed rail environment. Graphical abstract: Image, graphical abstract